2014
DOI: 10.1097/mou.0000000000000040
|View full text |Cite
|
Sign up to set email alerts
|

Can MRI replace serial biopsies in men on active surveillance for prostate cancer?

Abstract: MRI is useful in the identification of men with higher-risk prostate cancer prior to commencement of a formal active surveillance programme. It is also of use in following up men on active surveillance, as a way to detect change in tumour over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 32 publications
1
19
0
1
Order By: Relevance
“…7 Few studies to date have evaluated serial mpMRI findings in men with low risk PCa 812 and these questions remain largely unanswered. In this study we assessed whether changes in serial mpMRI can help predict the pathological progression of PCa in men on AS.…”
mentioning
confidence: 99%
“…7 Few studies to date have evaluated serial mpMRI findings in men with low risk PCa 812 and these questions remain largely unanswered. In this study we assessed whether changes in serial mpMRI can help predict the pathological progression of PCa in men on AS.…”
mentioning
confidence: 99%
“…Other authors have also reported higher sensitivity for high-grade tumor and more reliable confirmation of low-risk disease using MRI and subsequent targeted biopsy (32,33). Indeed, improved risk stratification in the AS setting may be considered one of the primary applications of prostate MRI and targeted biopsy in clinical practice today (34,35). The greater accuracy of MRI-targeted biopsy for clinically significant cancer reduces uncertainty and anxiety associated with a low-risk biopsy result.…”
Section: Improved Risk Stratification and Treatment Selection Using Mrimentioning
confidence: 94%
“…1 Meanwhile, recent reports suggests that ADC maps of DWI sequences, when not concerning, provide a high negative predictive value to rule out occult higher grade disease. 20,21 This has led to enthusiasm to replace the confirmatory biopsy with a staging mpMRI. However, a recently published study from Memorial Sloan Kettering raises concerns with such an approach.…”
Section: Multi-parametric Magnetic Resonance Imagingmentioning
confidence: 99%